2019
DOI: 10.3390/metabo9010006
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolomics Reveal the Antipyretic Effects of Jinxin Oral Liquid in Young Rats by Using Gas Chromatography–Mass Spectrometry

Abstract: Pyrexia is considered as a part of host’s defense response to the invasion of microorganisms or inanimate matter recognized as pathogenic or alien, which frequently occurs in children. Jinxin oral liquid (JXOL) is a traditional Chinese medicine formula that has been widely used to treat febrile children in China. Experimental fever was induced by injecting yeast into young male Sprague-Dawley rats (80 ± 20 g) and the rectal temperature subsequently changed. Four hours later, the excessive production of interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Our recent reports of plasma metabolomics indicated that XFZYD exerts neuroprotective effects on the controlled cortical impact (CCI) rats model via multiple pathways (Feng et al, 2017;Fu et al, 2019). However, due to the blood-brain barrier, the metabolic alterations in the biofluid may not be in parallel with that in the injured brain (Qian et al, 2019). In this regard, the analysis of brain samples to provide direct information on metabolism is available (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent reports of plasma metabolomics indicated that XFZYD exerts neuroprotective effects on the controlled cortical impact (CCI) rats model via multiple pathways (Feng et al, 2017;Fu et al, 2019). However, due to the blood-brain barrier, the metabolic alterations in the biofluid may not be in parallel with that in the injured brain (Qian et al, 2019). In this regard, the analysis of brain samples to provide direct information on metabolism is available (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophan, as an important amino acid, has the function of nourishing nerve and reducing excitotoxicity. When the rats were injected with yeast, the levels of quinolic acid upregulated [18], and quinolic acid produced tryptophan degradation through the kynurenine pathway [19]. The tryptophan content of LMA was increased significantly after frost, which could supplement the degradation of tryptophan and correct the disorder state induced by fever in rats.…”
Section: Resultsmentioning
confidence: 99%
“…3-Phosphoglyceric acid is a precursor for serine, which is an endogenous ligand of NMDA-R. Serine concentration in mouse cerebellum is very low (Fernandes and Gupta 2019 ); however, no change in serine was found in the hippocampus of UCMS rats in this study. The feasibility of using the precursor 3-phosphoglyceric acid content in the hippocampus instead of its content for testing is unknown, but it is certain that L-serine can protect neuronal cells against oxidative stress–mediated apoptotic cell death by contributing to intracellular antioxidant GSH synthesis and maintaining the mitochondrial fusion-fission balance (Qian et al 2019 ). It can support human cognitive functions, including formation of short-term memory, consolidation of long-term memory, learning and recalling information, and development of language and communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation for GC-MS analysis was revised according to previous reports (Qian et al 2019 ). Briefly, 20 mg of frozen hippocampus was homogenized in 500 μL of MeOH, and 20 μL of ice methanol containing 1,2- 13 C 2 -myristic acid was added to a final concentration of 10 μg/mL and vortexed for 5 min.…”
Section: Methodsmentioning
confidence: 99%